2013
DOI: 10.4103/2156-7514.106614
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Amniotic Fluid Index and Ultrasound Estimated Fetal Weight in Healthy Pregnant African Women

Abstract: Introduction:Fetal weight (FW) estimation in late pregnancy is an important guide in obstetric care. Amniotic fluid protects the fetus against traumatic and infective insults. There possibly exists a relationship between FW and amniotic fluid index (AFI) that can be estimated by ultrasonography.Materials and Methods:Two hundred and fifty-eight low-risk pregnancies were prospectively studied by means of ultrasound over a 12-month period. FW was estimated using a combination of fetal parameters; bi-parietal diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
8
1
Order By: Relevance
“…Ademola et al. ( 24 ) found an overall correlation coefficient between AFI and the EFWT to be 0.241 ( P > 0.05). He neither categorized the data into male and female nor grouped the data into gestational age groups.…”
Section: Discussionmentioning
confidence: 96%
“…Ademola et al. ( 24 ) found an overall correlation coefficient between AFI and the EFWT to be 0.241 ( P > 0.05). He neither categorized the data into male and female nor grouped the data into gestational age groups.…”
Section: Discussionmentioning
confidence: 96%
“…Previous reports have investigated possible associations between the sonographically attained fluid index and the EFW,[ 10 11 ] including the influence of AFI on the accuracy of sonographically EFW, among Caucasians. However, such studies are rare among Indians, especially those in Central India.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies by Adeyekun et al . 9 , in 2013 with 253 patients, or by Owen et al . 11 in 2002 with 274 patients, found no correlation between EFW and AFI, either in the overall population or in the gestational age-separated subgroups, which is discordant to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Such an association could indicate that the amniotic fluid assessment should consider the fetal parameters to make it more precise. A review of the existing literature showed conflicting results on the possible correlation between the amount of amniotic fluid and fetal weight estimation 9 – 12 . However, these studies were all unicentric, based only on a small number of patients (from 90 to 400 patients), mainly retrospective and did not analyze the influence of other factors.…”
Section: Introductionmentioning
confidence: 99%